Relative Performance Evaluation and Executive Compensation: Adding Fuel to the Fire - Werner Bönte; Dmitrii Galkin (Managerial and Decision Economics, 2025)
In this experimental study, we compare the effects of a compensation scheme based on relative performance evaluation (RPE) and a compensation scheme based on absolute performance evaluation (APE) on decision-making in a market game. To this end, we conduct an online experiment using the strategy method to obtain individual responses in a duopoly market with quantity competition. Our results point to a causal effect of the RPE-based compensation scheme on quantity decisions: subjects opt for higher quantities when incentivised by the RPE-based compensation scheme. While this observation is consistent with the theoretical predictions, our data imply that subjects deviate from payoff maximisation under both compensation schemes. Specifically, we find strong evidence that the RPE-based compensation system, in particular, increases the likelihood that subjects sacrifice their payoffs to reduce the competitors' payoffs (i.e., behave over -aggressively). Our results suggest that RPE-based remuneration structures, which are gaining traction in practice, may have unintended behavioural effects and can be detrimental to the profits of firms that use them.
Keywords: 650; experimental economics; incentive contract; managerial compensation; oligopoly theory; relative performance evaluation